Design of Self‐Floating Photothermal Conversion Devices with Solar Steam Generation Capability. Issue 10 (16th December 2021) - Ge, Bo; Han, Baobao; Lv, Jing; Zhao, Limin; Yin, Yibin; Ren, Guina; Zhang, Zhaozhu
Abstract: Aiming to tackle water pollution from toxic and harmful substances and the lack of clean water, a multifunctional device is designed. The superhydrophobic fabric (M‐fabric) is taken as the floating layer. The contact angle of the water droplet on the surface of the M‐fabric is 160°, and the recovery of organic solvent can be realized by superhydrophobicity and superoleophilicity. The oil/water separation efficiency is 97.7% and the stability of the superhydrophobic fabric is confirmed. Due to the existence of Bi2 WO6, the M‐fabric can photodegrade soluble pollutants. Based on the detailed analysis of the photoresponse ability, carrier fluorescence lifetime (1.95 ns), and reaction rate constant, the reaction mechanism is proposed. Importantly, the assembled photothermal device has a high rate of solar steam generation for the initially treated sewage. It is hoped that the multi‐component synergy can provide new ideas on environmental governance and clean water production. Abstract : The assembled photothermal conversion device solves the problem of producing clean water vapor under sewage conditions. Efficient oil/water separation and photodegradation capability are obtained.